A simple prognostic score for COVID-19 hospitalized patients developing deep vein thrombosis. (December 2021) - Bozzani, Antonio; Arici, Vittorio; Tavazzi, Guido; Boschini, Stefano; Guglielmi, Angelo; Mazza, Giovanni; Mojoli, Francesco; Bruno, Raffaele; Ragni, Franco; Sterpetti, Antonio V
Objective: The aim of our study was to analyze the specificity, accuracy and sensitivity of a simple, easy to calculate, prognostic score for hospitalized COVID19 patients developing deep vein thrombosis. Methods: From March 1st to April 28th, 942 COVID-19 patients with severe symptoms were admitted to the hospital San Matteo of Pavia-Italy. Thirty two patients (3.4%) developed deep vein thrombosis during hospitalization. In all patients hemostatic and inflammatory parameters were abnormal. A simple prognostic score was developed based on the presence of specific co morbidities and D-dimers levels (quick San Matthew Score-quick SMS): Results: Nine patients died in a condition of multiple organ failure, 23 patients (71.9%) survived and left the hospital in good general conditions. The developed score was based simply on two parameters: 1) presence of four specific co morbidities and 2)systemic levels of D-Dimers. The quick San Matthew Score resulted in a sensitivity, specificity and overall accuracy of more than 90% (94%, 92%, 93% respectively) and compared favorably with other scores. The score was prospectively validated in 100 COVID19 patients who developed deep vein thrombosis collected from the literature and prospectively confirmed in our hospital. Conclusions: The findings of our study underline the importance of an immediate aggressive therapeutic approach for moderate and high-risk patients with COVID19 infection. The quick SMS score may help to identify patients at high risk for mortality and to follow the clinical outcome of the patient. A simple, easy to calculate prognostic score may also facilitate communication among health workers.